The success and shortcomings of democratic development in Nigeria from 1960 to 1999: An overview. - Osinakachukwu, Nwokeke P.; Jawan, Jayum; Redzuan, Ma'rof (Canadian Center of Science and Education (CCSE), 2011)
This paper examines democratic development in Nigeria between 1960 and 1999. It discusses various democracies and some of the shortcomings inherent in their implementations. This work adopts a qualitative approach using both content and historical analysis to analyze secondary sources gathered on both civilian and military regimes as they affected democratic performances in Nigeria. This paper aims at helping policy makers in carrying out policies that will help strengthen the electoral bodies/conducts, respect the rule of law/constitution, ensure good governance which will improve leadership qualities and cement democratic values in the nation hence evidence from findings indicate that democracy have failed to triumph in Nigeria due to reasons emanating from bad governance and lack of democratic values. The paper provides some plausible recommendations that will be of particular benefit to policy makers and to general interest of Nigeria if properly implemented.